Industrial canvas and its manufacturing method
The canvas design with alternately arranged yarns and a polymer alloyed resin coating addresses tear strength and durability issues, providing enhanced performance at extreme temperatures and appearance balance.
Patent Information
- Application Number
- JP2023150633
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-09-18
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-09-18
AI Technical Summary
Existing canvases for industrial applications, such as tent warehouses, house tents, and truck bed covers, face challenges with inadequate tear strength, bending durability, especially at sub-zero temperatures, and joint durability under hot conditions, while also requiring a balance between glossy and diffusely reflective areas.
A canvas design featuring alternately arranged multifilament and short fiber spun yarns with a soft vinyl chloride resin impregnated coating layer containing a rubber component, which includes a polymer alloy formed by intertwining the molecular chains of cured liquid rubber with the vinyl chloride resin main chain, and optionally incorporating silica particles for enhanced adhesion and durability.
The canvas achieves balanced tear strength in both warp and weft directions, superior bending durability at sub-zero temperatures, and joint durability under hot conditions, maintaining appearance quality with reduced weight compared to conventional products.
Smart Images

Figure 0007616706000001 
Figure 0007616706000002 
Figure 0007616706000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a canvas for industrial materials used as the main material for tent warehouses (simple houses), rooftop tents (assembly tents with awnings attached that are used for athletic meets, outdoor events, management headquarters, assemblies, reception desks, etc.), truck canopies, truck bed covers, open-air storage sheets, etc., which has excellent balance of tear strength in the warp and weft directions and bending durability (resistance to flapping), especially bending durability (resistance to flapping) below freezing and joint durability (resistance to peeling at sewn parts) under the blazing sun, and a method for manufacturing the same. [Background technology]
[0002] For the main body material of tent warehouses, roofed tents, truck hoods, truck bed covers, open-air storage sheets, etc., No. 4 to No. 6 canvas, which is made by impregnating and coating No. 4 to No. 6 spun cloth with a soft polyvinyl chloride resin composition, is used. These have a thickness of 0.38 to 0.55 mm and a mass of 420 to 560 g / m 2 The standard is mainstream, and the smaller the number, such as No. 6, No. 5, and No. 4, the heavier and more durable the canvas. The fabric used for these canvases is woven from short fiber spun yarns with a lot of fluff, and the soft polyvinyl chloride resin composition has a high impregnation and coating effect, which gives the canvas its bending strength and bending durability. This bending strength and bending durability exceed those of tarpaulin, but the tear resistance (tear strength) of canvas is inferior to that of tarpaulin, which is based on a fabric woven with multifilament yarn. Therefore, in the above-mentioned applications, the larger the application scale (size), the more emphasis is placed on toughness and tear resistance, and a rank up from No. 6 to No. 5, and from No. 5 to No. 4 canvas is sometimes used. This means an increase in mass for large applications, and especially in applications such as house tents, truck bed covers, and open-air storage sheets, which are folded and stored when stored, the manual transportation, spreading, and installation of the sheets, and their removal, are a huge burden of work. Therefore, for these applications, there is a strong demand for lighter, more durable canvas, for example, a canvas with the weight of No. 6 but the toughness and durability of No. 5, or similarly, a canvas with the weight of No. 5 but the toughness and durability of No. 4.
[0003] In response to such needs, the applicant proposed an invention (Patent Document 1) for a canvas with excellent tear strength due to soft polyvinyl chloride resin processing, in which the weave structure contains parallel yarns consisting of two staple spun yarns, the warp and weft contain parallel yarns, and at least the intersection point of the warp and weft contains a portion composed of four staple spun yarns. In this invention, when comparing canvases using the same fabric size (mass) (Example 1 / Comparative Example 1, Example 2 / Comparative Example 2), a canvas with superior tear strength was obtained, and the effects of the invention were described as being that a canvas was obtained that could exhibit the same tear strength as conventional products while using a lighter fabric than conventional products. For a long time, there have been proposals for tarpaulins that combine the peel strength between the base fabric and the resin and the tear strength, such as a specification in which continuous yarns and staple fiber yarns are arranged alternately as the warp and / or weft threads, with staple fibers accounting for 5 to 90% by weight of the fabric, and a laminated resin layer (Patent Document 2). Similarly, as a high-strength canvas, a specification has been proposed in which staple fiber yarns and long fiber yarns are arranged alternately or in a lattice pattern, with staple fiber yarns accounting for 5 to 95% by weight and long fiber yarns accounting for 95 to 5% by weight, and then waterproofed (Patent Document 3). However, it was not clear how to achieve a good balance between the appearance quality determined by the amount of each thread (balance between glossy and diffusely reflective areas), the peel strength between the base fabric and the resin, and the tear strength. Recently, a flexible laminate that is excellent in strength, water resistance, flexibility, and durability, and has improved lightness due to soft polyvinyl chloride resin processing has been developed. The warp and weft yarns constituting the fiber fabric contain one or more selected from spun yarns and multifilament yarns, the content ranges of spun yarns and multifilament yarns relative to the mass of the fiber fabric are individually specified, and the basis weight of the flexible laminate is 300 g / m 2 More than 450g / m 2 In this invention, the flexible laminate in the embodiment has a basis weight of 450 g / m 2It is described that the weight is less than 10% to 25% lighter than the conventional flexible laminate of the comparative example, and the tensile strength, tear strength, and elongation are all equivalent to those of the conventional flexible laminate. However, the invention of Patent Document 4 mainly uses a plain weave base fabric with spun yarn for the warp and multifilament yarn for the weft as Examples 1 to 4, so that in order to achieve a balance in tear strength in the warp and weft directions, it is time-consuming to adjust the yarn strength (fineness) and thread count (yarn arrangement density) in the warp and weft directions, and the appearance has directionality, with streaks in the glossy and diffuse reflection areas being emphasized depending on the angle.
[0004] The tarpaulins and canvases of Patent Documents 1 to 4 can improve physical properties such as tear strength and reduce weight by improving the weave structure of the fabric and using different types of yarns in combination. However, to further reduce weight, it is directly effective to reduce the thickness of the resin coating layer made of soft polyvinyl chloride resin with a high specific gravity. However, the thinner the resin coating layer, the worse the bending resistance, abrasion resistance, and joint durability (safety that the sewing part is unlikely to peel off and break), and it is likely to cause problems such as water leakage (rain leakage) from cracks and abrasion scratches, and sewing part breakage. In order to avoid these problems, it is essential to reduce weight (thinning) after improving the bending resistance and abrasion resistance of the resin coating layer itself, and if the soft polyvinyl chloride resin coating layer can be made stronger, it will be possible to reduce weight (thinning) to a certain extent without impairing durability. Regarding the toughening of the soft vinyl chloride resin coating layer, the present applicant previously disclosed in Patent Document 5 that the soft vinyl chloride resin layer contains a polyol compound, and a triisocyanate compound undergoes an addition reaction with the polyol compound to generate a crosslinked urethane component in the soft vinyl chloride resin layer, thereby improving the abrasion resistance, heat resistance, impact resistance, etc. of the soft vinyl chloride resin layer. The generation of this crosslinked urethane component improves the heat resistance and toughness of the soft vinyl chloride resin layer, but on the other hand, the texture becomes hard in cold weather, and the soft vinyl chloride resin layer is vulnerable to cracking due to dynamic stress such as repeated bending, folding, and flapping, especially below freezing. This is considered to be due to the glass transition temperature difference between the soft vinyl chloride resin and the crosslinked urethane, and furthermore, the compatibility is significantly deteriorated below freezing. Therefore, there has been a need to improve the toughness of the soft vinyl chloride resin layer and improve it so that it is less likely to crack even when subjected to dynamic stress below freezing, but this has not yet been resolved. If the problem of cracking at sub-freezing temperatures can be solved, it will be possible to obtain a canvas that has excellent bending durability (resistance to flapping) and can be easily folded and stored. This will lead to improved service lives for tent warehouses, rooftop tents, truck canopies, truck bed covers, open-air storage sheets, etc., and is expected to contribute to the creation of an environmentally conscious society that reduces carbon dioxide emissions. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication No. 2021-017668 [Patent Document 2] Japanese Utility Model Application Publication No. 48-61171 [Patent Document 3] Japanese Utility Model Application Publication No. 51-124169 [Patent Document 4] Patent Publication No. 2022-057803 [Patent Document 5] JP 2015-205428 A Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention is to provide a canvas for industrial materials that has an excellent balance of tear strength in the warp and weft directions and bending durability (resistance to flapping), particularly bending durability (resistance to flapping) below freezing points and joint durability (resistance to peeling at sewn parts) under the blazing sun, and also has an excellent appearance quality (balance between glossy parts and diffuse reflection parts), and a method for manufacturing the same, and can be used as the main material for tent warehouses (simple houses), rooftop tents (assembly tents with awnings that can be used for sports days, outdoor events, management headquarters, assemblies, reception desks, etc.), truck canopies, truck bed covers, open-air storage sheets, etc. [Means for solving the problem]
[0007] As a result of careful research and consideration of these points, the inventors discovered that a canvas designed in such a way that multifilament yarns and staple spun yarns are regularly alternately arranged in the fabric and that a rubber component is contained in the soft polyvinyl chloride resin impregnated coating layer can be used to obtain a canvas for industrial materials that has excellent balance of tear strength in the warp and weft directions and bending durability (resistance to fluttering), particularly bending durability (resistance to fluttering) below freezing points and joint durability (resistance to peeling at sewn parts) under the blazing sun, and also has excellent appearance quality (balance between glossy parts and diffuse reflection parts), which led to the completion of the present invention.
[0008] The canvas for industrial materials of the present invention is a canvas having a soft polyvinyl chloride resin-impregnated coating layer on the entire surface of the fabric, the fabric being woven from a warp yarn group and a weft yarn group, and multifilament yarns and staple spun yarns are regularly alternately arranged in both warp and weft yarn groups, the number of repeating units in this alternating arrangement being 2 to 6, the alternating arrangement being any one of nine combinations of the multifilament yarns (1 to 3 yarns) and the staple spun yarns (1 to 3 yarns), and the soft polyvinyl chloride resin-impregnated coating layer containing a liquid rubber cured product. The cured liquid rubber is a polymer of one or more reactive liquid rubbers selected from the group consisting of butadiene-based, isoprene-based, and farnesene-based, and is also a composite of the reactive liquid rubber and silica particles, which is a reaction product of the reactive liquid rubber and silanol groups (Si-OH groups) on the surface of the silica particles. It is preferable that the multifilament yarn constituting the ply-twisted yarn is a factor that governs the strength, elongation, and tear strength of the canvas, and the staple spun yarn is a factor that governs the bending durability of the canvas, and in particular the amount of fluff is a factor that governs the adhesion between the fabric and the soft polyvinyl chloride resin-impregnated coating layer, i.e., the anchoring effect. In the present invention, particularly when the multifilament yarn is a bulky yarn or a twisted yarn having a bulky portion on the outer periphery, it is useful in that it combines the factors that govern the strength, elongation, and tear strength of the canvas, and the factors that govern the bending durability of the canvas and the adhesion between the fabric and the soft polyvinyl chloride resin-impregnated coating layer, as the bulky portion plays the role of fluff. The bulky multifilament yarn is a taslan-processed yarn or a woolly-processed yarn, and the twisted yarn having a bulky portion on the outer periphery is a core-spun core-sheath processed yarn, which is obtained by twisting a spun yarn around the outer periphery of the multifilament yarn. By forming a polymer alloy in which the molecular chains of the liquid rubber cured product are entangled with the vinyl chloride resin main chain within the soft polyvinyl chloride resin-impregnated coating layer, it is possible to obtain a canvas for industrial materials that has excellent flexural durability (flutter resistance) and abrasion resistance even when the soft polyvinyl chloride resin-impregnated coating layer is made lighter, and is particularly excellent in flexural durability (flutter resistance) below freezing points and joint durability (resistance to peeling at sewn parts) under the blazing sun. According to this embodiment, even if the soft polyvinyl chloride resin-impregnated coating layer is designed to be thinner than conventional products to reduce the weight of the canvas, it is possible to obtain durability equivalent to that of conventional products.
[0009] In the canvas for industrial materials of the present invention, the multifilament yarn is preferably a bulky yarn or a core-sheath yarn having a bulky portion on the outer periphery. The anchoring effect of the fluff of the staple spun yarn and the anchoring effect of the bulky multifilament yarn work synergistically to more firmly bond and integrate the soft polyvinyl chloride resin-impregnated coating layer with the surface of the fabric, thereby making it possible to obtain superior bending durability (resistance to fluttering) and superior joint durability (resistance to peeling at the sewn portion). The bulky multifilament yarn can be formed by any of taslan processing, woolly processing, and core-spun core-sheath processing. The yarn having a bulky portion can be a mixed twist of a bulky multifilament yarn and a normal multifilament yarn.
[0010] In the canvas for industrial materials of the present invention, the liquid rubber cured product is preferably a polymer of one or more reactive liquid rubbers selected from butadiene-based, isoprene-based, and farnesene-based. By forming a polymer alloy in which the molecular chains of the rubber component are entangled with the main chain of the vinyl chloride resin within the soft polyvinyl chloride resin impregnated coating layer, it is possible to obtain a canvas for industrial materials that has excellent flexural durability (flutter resistance), particularly flexural durability (flutter resistance) below freezing points and joint durability (resistance to peeling at sewn parts) under the blazing sun.
[0011] In the industrial canvas of the present invention, the liquid rubber cured product is preferably a composite with silica particles. By reacting with the silanol groups (Si-OH groups) on the surface of the silica particles and becoming part of the liquid rubber cured product, the liquid rubber cured product becomes tougher, improving its flexural durability (flutter resistance) and abrasion resistance, and also improving the cold resistance and heat resistance (softening temperature) of the soft polyvinyl chloride resin impregnated coating layer. This improved heat resistance not only improves the peel strength of the joint where industrial canvases are heat-sealed and lap-joined, but also improves the durability of the joint under the hot sun (resistance to peeling of the sewn part).
[0012] The manufacturing method of the canvas for industrial materials of the present invention is a canvas in which a soft vinyl chloride resin-impregnated coating layer is formed on the entire surface of a fabric containing multifilament yarns and staple spun yarns in a regularly alternating arrangement, and the manufacturing method includes the steps of: 1) preparing a soft vinyl chloride resin composition containing at least three types of vinyl chloride resin, a plasticizer, and a reactive liquid synthetic rubber (one or more selected from butadiene-based, isoprene-based, and farnesene-based), 2) coating the fabric with the soft vinyl chloride resin composition to form a soft vinyl chloride resin-impregnated coating layer. (Before gelation) 3) forming a Simultaneously with the gelling heat treatment of the soft vinyl chloride resin composition for forming the soft vinyl chloride resin-impregnated coating layer, The reactive liquid synthetic rubber is preferably converted into a rubber cured product to impregnate the entire soft vinyl chloride resin impregnated coating layer with a synthetic rubber component. After coating, the reactive liquid synthetic rubber molecules are present in the soft vinyl chloride resin impregnated coating layer in a state where they are entangled with the vinyl chloride resin main chain, and by curing this reactive liquid synthetic rubber, a polymer alloy in which the molecular chains of the synthetic rubber are entangled with the vinyl chloride resin main chain can be effectively formed throughout the entire soft vinyl chloride resin impregnated coating layer, resulting in an industrial canvas that is excellent in bending durability (flutter resistance) and abrasion resistance, and is particularly excellent in bending durability (flutter resistance) below freezing points and joint durability (difficulty in peeling off the stitched parts) under the blazing sun. This also makes it possible to reduce the weight by one rank without compromising performance.
[0013] In the manufacturing method of the canvas for industrial materials of the present invention, the fabric is woven with a warp yarn group and a weft yarn group, and the warp and weft yarn groups contain multifilament yarns (including bulky yarns and core-sheath yarns having a bulky portion on the outer periphery) and staple spun yarns in an alternating arrangement, and the number of repeating units in this alternating arrangement is 2 to 6, and it is preferable that the alternating arrangement is any one of nine combinations of the multifilament yarns (1 to 3 yarns) and the staple spun yarns (1 to 3 yarns). This makes the tear strength balance in the warp and weft directions balanced and can be adjusted as desired. The soft vinyl chloride resin-impregnated coating layer of the multifilament yarns forms a glossy portion, and the soft vinyl chloride resin-impregnated coating layer of the staple spun yarns forms a diffuse reflection portion, and the balance between the glossy portion and the diffuse reflection portion directly determines the quality of the appearance, so by adopting the above alternating arrangement, it is possible to stabilize the quality of the appearance.
[0014] In the manufacturing method of the canvas for industrial materials of the present invention, it is preferable to add silica particles to the soft polyvinyl chloride resin composition and convert it into a composite rubber cured product with the silica particles. The silanol groups (Si-OH groups) on the surface of the silica particles react with the functional groups of the liquid synthetic rubber to form a synthetic rubber component / silica particle hybrid, while the molecular chains of the synthetic rubber are entangled with the main chain of the polyvinyl chloride resin to form a polymer alloy, which strengthens the soft polyvinyl chloride resin-impregnated coating layer, improving its bending durability (flutter resistance) and abrasion resistance, and also improving the cold resistance and heat resistance (softening temperature) of the soft polyvinyl chloride resin-impregnated coating layer. This improvement in heat resistance not only improves the peel strength of the joint where the industrial canvases are heat-sealed and lap-joined, but also improves the durability of the joint under the blazing sun (resistance to peeling of the sewn part). If the thermal fastness of this joint is insufficient, peeling and destruction of the joint in a tent warehouse, truck hood, etc. may occur. Effect of the Invention
[0015] The present invention provides an industrial canvas that has excellent balance of warp and weft tear strength, and flexural durability (resistance to flapping), particularly at sub-zero temperatures, and excellent joint durability under the hot sun (resistance to peeling at sewn parts), and also has a good appearance (balance between glossy and diffuse reflection parts), making it possible to use it widely as the main body material for tent warehouses (simple houses), roofed tents (assembly tents with awnings used for athletic meets, outdoor events, management headquarters, assemblies, receptions, etc.), truck hoods, truck bed covers, open-air storage sheets, etc. Furthermore, the present invention provides a canvas that has the same durability as conventional products, even if the canvas is made lighter by designing the soft polyvinyl chloride resin-impregnated coating layer to be thinner than conventional products. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The canvas for industrial materials of the present invention is a canvas having a soft polyvinyl chloride resin-impregnated coating layer provided on the entire surface of the fabric, the fabric being woven from a group of warp threads and a group of weft threads, with multifilament yarns and staple spun yarns arranged alternately in both the warp and weft thread groups, the alternating arrangement having 2 to 6 repeating units and being any one of nine combinations of multifilament yarns (1 to 3 threads) and staple spun yarns (1 to 3 threads), the soft polyvinyl chloride resin-impregnated coating layer containing a liquid rubber cured product, in particular in a mode in which the multifilament yarns have bulky portions, and in particular in a mode in which the liquid rubber cured product is composited with silica particles. The manufacturing method of these industrial canvases includes: 1) a step of preparing a soft polyvinyl chloride resin composition containing at least three components: polyvinyl chloride resin, a plasticizer, and a reactive liquid synthetic rubber; 2) a step of applying the soft polyvinyl chloride resin composition to a fabric to form a soft polyvinyl chloride resin-impregnated coating layer; and 3) a step of converting the reactive liquid synthetic rubber into a cured rubber material to impregnate the entire soft polyvinyl chloride resin-impregnated coating layer with the synthetic rubber, as well as a step of incorporating silica particles into the soft polyvinyl chloride resin composition to convert it into a cured composite rubber material with the silica particles.
[0017] The fabric used for the canvas for industrial materials of the present invention is a fabric woven from a warp thread group and a weft thread group, in which multifilament threads and staple spun threads are regularly alternately arranged in both warp and weft thread groups, with the number of alternately arranged repeat units being 2 to 6 and the void ratio being 0 to 15% (such as plain weave, twill weave, satin weave, twill weave, basket weave, etc.). More specifically, the alternate arrangement of the warp thread group is any one of nine combinations of multifilament threads (1 to 3 threads) and staple spun threads (1 to 3 threads), and the alternate arrangement of the weft thread group is any one of nine combinations of multifilament threads (1 to 3 threads) and staple spun threads (1 to 3 threads). Specifically, the alternating arrangement of the multifilament yarns (represented as M) and staple spun yarns (represented as S) in the warp yarn group and the weft yarn group is nine types of repeating units: "MS (2 yarns, 1:1)", "MSS (3 yarns, 1:2)", "MSSS (4 yarns, 1:3)", "MMS (3 yarns, 2:1)", "MMSS (4 yarns, 1:1)", "MMSSS (5 yarns, 2:3)", "MMMS (4 yarns, 3:1)", "MMMSSS (5 yarns, 3:2)", and "MMMSSS (6 yarns, 1:1)". The ratio of the number of multifilament yarns and staple spun yarns included in the warp yarn group (or weft yarn group) is 1:3 to 3:1, preferably 2:3 to 3:2, and particularly preferably 1:1, when they have the same fineness (or the same count). The multifilament yarns constituting the alternating arrangement are the factors that govern the strength, elongation, and tear strength of the canvas, while the staple spun yarns are the factors that govern the bending durability of the canvas, and in particular the amount of fuzz, the adhesion between the fabric and the soft polyvinyl chloride resin-impregnated coating layer, and it is up to the user to decide which balance between the two is to be. The soft polyvinyl chloride resin-impregnated coating layer on the multifilament yarn portion forms the glossy portion, and the soft polyvinyl chloride resin-impregnated coating layer on the staple spun yarn portion forms the diffuse reflection portion, and the balance between the glossy portion and the diffuse reflection portion directly determines the quality of the appearance, so by adopting the above alternating arrangement, a better quality of appearance can be obtained.
[0018] In particular, in order to balance the tear strength in the warp and weft directions, it is preferable to use the same alternating arrangement (repeat unit) in the warp yarn group and the weft yarn group, so that the number of multifilament yarns that contribute to tear strength is 1:1 in the warp:weft. When emphasis is placed on the strength, tear strength, and glossy appearance of the canvas, a repeat unit (alternating arrangement) in which the number of multifilament yarns is greater than that of staple spun yarns is preferable, specifically "MMS (3 strands)" or "MMMSS (5 strands)" for both the warp yarn group and the weft yarn group. On the other hand, when emphasis is placed on the bending durability (resistance to flapping), joint durability (resistance to peeling at the stitching), and appearance with diffuse reflection, a repeating unit (alternating arrangement) in which the number of short fiber spun yarns having fluff that contributes to the anchoring effect is greater than that of the multifilament yarns is preferred, specifically, "MSS (3 strands)" or "MMSSS (5 strands)" for both the warp yarn group and the weft yarn group. To adopt the optimal balance of the features of both, repeating units (alternating arrangements) such as "MS", "MMSS", and "MMMSSS" are preferred. In particular, the tear strength of multifilament yarns and short fiber spun yarns is dramatically increased by arranging them in 2 strands or 3 strands, so repeating units such as "MMSS (4 strands)", "MMSSS (5 strands)", "MMMSSS (5 strands)", and "MMMSSS (6 strands)" are preferred. In addition, in repeat units with a thread count ratio of 1:2 or 1:3, such as "MSS (3 threads)," "MMS (3 threads)," "MMMS (4 threads)," and "MSSS (4 threads)," the imbalance in tear strength can be improved by increasing the fineness of the fewer multifilament yarn by 2 to 3 times, or by lowering the rank of the count of the staple spun yarn, or by using a two-ply yarn or a three-ply twist.
[0019] In particular, it is preferable that the multifilament yarn has a bulky portion, and the anchoring effect of the fluff of the staple spun yarn and the anchoring effect of the bulky portion of the multifilament yarn work synergistically to more strongly bond and integrate the soft polyvinyl chloride resin-impregnated coating layer with the surface of the fabric, thereby making it possible to provide superior bending durability (resistance to fluttering) and also superior joint durability (resistance to peeling at the sewn portion). Such bulky portions can be formed by taslan processing, woolly processing, or core spun core-sheath processing. Taslan processing is a method in which compressed air is blown onto a multifilament yarn to entangle the filaments in a loop shape to form a bulky section, woolly processing is a method in which a multifilament yarn is twisted and heat-set, and then the twist is reversed to form a bulky section, and core-spun core-sheath processing is a method in which a multifilament long fiber yarn is used as a core and short fiber staples are entangled all around it to form a bulky section of a pseudo-short fiber spun yarn with a core-sheath structure in a mass ratio of 10:1 to 2:1. All of these bulky yarns have the strength (tear resistance) of a multifilament (long fiber yarn), but have hooks (fuzz or loose bulk) equivalent to the fuzz of short fiber spun yarn, which gives them the advantage of providing an anchoring effect to the soft polyvinyl chloride resin-impregnated coating layer, and at the same time, the soft polyvinyl chloride resin-impregnated coating layer that covers the bulky yarn provides the diffuse reflection part of the canvas appearance.
[0020] The fiber types of the multifilament yarn (non-bulky or bulky) and the staple spun yarn include synthetic fibers (various polymers, recycled polymers), natural fibers (cotton, kenaf), semi-synthetic fibers (rayon), and inorganic fibers (glass fibers, carbon fibers, etc.). In particular, synthetic fibers such as polypropylene fibers, polyethylene fibers, vinylon fibers, polyester fibers, nylon fibers, acrylic fibers, and polyurethane fibers are preferred in terms of the balance between versatility and physical properties, and polyester fibers (particularly polyethylene terephthalate, and furthermore, recycled polyethylene terephthalate obtained by depolymerizing recycled polyethylene terephthalate and polymerizing the recycled monomer), nylon fibers, and vinylon fibers are particularly preferred. In particular, in order to dramatically improve the tear resistance of the fabric, high-strength multifilament yarns of wholly aromatic polyester fibers (polyarrelate), wholly aromatic polyamide fibers (aramid), and aromatic heterocyclic polymer fibers (polybenzoxazole, polybenzimidazole, polybenzothiazole, etc.) can be used. Furthermore, in a fabric (woven material) using a multifilament yarn of polyester fiber, a ripstop fabric designed by replacing the multifilament yarn at specific intervals in the warp yarn group and the weft yarn group with the above-mentioned high-strength multifilament yarn can also be used. In a core-spun yarn, which is a core-sheath yarn having a bulky portion on the outer periphery, the fiber type of the staple fiber used for the sheath is preferably the same as that of the core, but a different combination of, for example, a multifilament yarn of wholly aromatic polyamide fiber (aramid) for the core and a polyester staple fiber for the sheath may also be used.
[0021] The multifilament yarn may have a general-purpose fineness such as 250 denier, 500 denier, 750 denier, 1000 denier, or 1250 denier (278 dtex, 555 dtex, 833 dtex, 1111 dtex, or 1388 dtex), and is particularly preferably 500 denier, 750 denier, or 1000 denier (555 dtex, 833 dtex, or 1111 dtex), but is not limited to multiples of 250 denier. The filament single yarn of the multifilament yarn is 3 to 10 denier, preferably 4 to 6 denier, and for example, the number of filaments of a 500 denier yarn is about 50 to 166 (preferably about 83 to 125), and the larger the fineness number, the higher the strength (breaking strength, tear strength). The number of twists of the yarn is preferably 100 to 1000 times / m, particularly preferably 200 to 500 times / m, and in particular, the number of twists of the Taslan yarn is preferably 10 to 200 times / m, particularly preferably 20 to 100 times / m. If it exceeds 200 times / m, the bulky part will be tightly wound, impairing the anchor effect on the soft polyvinyl chloride resin impregnated coating layer. In addition, the staple spun yarn may be 10-count single yarn (590 dtex), 14-count single yarn (422 dtex), 15-count single yarn (394 dtex), 20-count single yarn (295 dtex), or 30-count single yarn (197 dtex), and in particular, 14-count, 15-count, and 20-count single yarn are preferred. Other examples include 14-count two-ply yarn (844 dtex), 15-count two-ply yarn (788 dtex), 20-count two-ply yarn (590 dtex), and 30-count two-ply yarn (394 dtex), with 20-count two-ply yarn and 30-count two-ply yarn being particularly preferred. The smaller the number, the higher the strength (breaking strength, tear strength). These are twisted yarns (doubled yarns, doubled yarns) with 100 to 1000 twists / m and a twist factor of 3.0 to 4.5, S (right) twist or Z (left) twist. The yarn pick density (multifilament yarns and staple spun yarns) of the fabric is 40 to 80 warp yarns, preferably 45 to 60, and 30 to 70 weft yarns, preferably 40 to 55, per inch, and the fabric mass is 170 g / m 2 ~410g / m 2 , preferably 190 g / m 2 ~260g / m 2 It is.
[0022] The fabric used may have been subjected to known fiber treatments such as scouring, bleaching, dyeing, softening, water repellency, waterproofing, flame retardancy, and calendaring. If the soft polyvinyl chloride resin-impregnated coating layer of the canvas is damaged by scratches, wear, cracks, or other damage, rainwater may seep in through the damaged area, causing water leakage problems. To prevent water leakage, the entire fabric is impregnated with a water repellent (0.3 to 6 g / m2). 2 ) to prevent water absorption. The water repellent is an emulsion of a perfluoroalkyl group-containing copolymer resin made by using an ethylenically unsaturated monomer having a perfluoroalkyl group or a perfluoroalkenyl group having 8 or less carbon atoms. Specifically, it is a copolymer of an acrylate and / or methacrylate having a perfluoroalkyl group having 8 or less carbon atoms and a monomer such as (meth)acrylic acid, (meth)acrylic acid ester, (meth)acrylamide, maleic acid or phthalic acid alkyl ester, vinyl chloride, vinylidene chloride, ethylene, or styrene. These water repellents obtain a high degree of water repellency by orienting and aligning the perfluoroalkyl group by thermal curing at 120 to 180°C. Other water repellents include silicone-based water repellents such as methylchlorosilane, methylpolysiloxane resin, dimethylpolysiloxane, and methylhydrogenpolysiloxane, paraffin-based water repellents such as n-paraffin wax with 20 to 48 carbon atoms and a melting point of 50 to 70°C, complexes of these paraffin-based compounds with zirconium, and other compounds such as alkylene urea compounds (octadecylethylene urea), aliphatic amide compounds (N-methylolstearylamide), polyvinylpyrrolidone, and water-absorbent resins (which suppress capillary action by swelling with water retention), such as sodium polyacrylate (crosslinked), carboxymethylcellulose crosslinked, and polyvinyl alcohol crosslinked. Water absorption prevention treatment can be performed by using different types of water repellents and forming two water-repellent layers, one on the inside and one on the outside, through two impregnation steps, or by forming a two-type mixed water-repellent layer through one impregnation step. The method of forming two water-repellent layers, inner and outer, is to temporarily form the inner layer by only drying treatment after the first impregnation, and then to perform thermal curing at 130 to 180°C all at once after the second impregnation and drying.
[0023] The soft vinyl chloride resin-impregnated coating layer provided on the entire surface of the fabric is formed by coating and heat treatment gelation of a soft vinyl chloride resin composition, or by dipping and heat treatment gelation. Here, the vinyl chloride resin refers to vinyl chloride resin, crosslinked vinyl chloride resin, chlorinated vinyl chloride resin, ethylene-vinyl chloride copolymer, vinyl acetate-vinyl chloride copolymer, acrylic-(graft)vinyl chloride copolymer, urethane-vinyl chloride (graft) copolymer, etc. The soft vinyl chloride resin composition is a liquid paste sol containing at least three types of vinyl chloride resin, plasticizer, and liquid synthetic rubber. Specifically, the soft polyvinyl chloride resin composition mainly contains a paste polyvinyl chloride resin (emulsion polymerization type, preferably a biomass synthetic product) having a number average molecular weight of 1000 to 2000, 40 to 100 parts by mass of a plasticizer (adipic acid ester compound, a phthalate ester compound, a cyclohexane dicarboxylate ester compound, a cyclohexene dicarboxylate ester compound, a phosphate ester compound, a chlorinated paraffin compound, a polyester compound, or the like, preferably a biomass synthetic product) relative to 100 parts by mass of the paste polyvinyl chloride resin, and 5 to 30 parts by mass of a liquid synthetic rubber (butadiene rubber, isoprene rubber, farnesene rubber, or the like, preferably a biomass synthetic product, which is later converted into a rubber cured product) relative to 100 parts by mass of the paste polyvinyl chloride resin.Other compounding agents include stabilizers (barium-zinc complexes, calcium-zinc complexes, epoxidized soybean oil, etc.), flame retardants (antimony trioxide, antimony pentoxide, aluminum hydroxide, magnesium hydroxide, zinc borate, etc.), fillers (calcium carbonate, barium sulfate, talc, etc.), UV resistance agents (benzophenone tautomers, benzotriazole tautomers, triazine tautomers, hindered amine compounds, etc.), adhesives (multifunctional isocyanate compounds, silane coupling agents, etc.), and mold inhibitors (imidazoles). Preferred are blended compositions containing any and any amounts of compounds such as ethylhexyl ether compounds, thiazole compounds, isothiazolinone compounds, pyridine compounds, N-haloalkylthio compounds, phenoxyarsine compounds, etc., pigments (titanium oxide, carbon black, inorganic compounds, azo compounds, phthalocyanine compounds, anthraquinone compounds, quinacridone compounds, etc.), to which known additives such as fluorescent whitening agents, antistatic agents, surfactants, antioxidants, chemical foaming agents, insect repellents, deodorants, and heat-shielding pigments can be added as necessary.
[0024] In order to improve the abrasion resistance of the soft polyvinyl chloride resin-impregnated coating layer, it is preferable to include 0.05 to 5.0 mass % of a lubricant relative to the soft polyvinyl chloride resin-impregnated coating layer. The lubricating effect of the lubricant reduces the friction coefficient of the soft polyvinyl chloride resin-impregnated coating layer, thereby reducing abrasion and extending the service life. If the amount added exceeds 3 mass %, it may deteriorate the printability on canvas (especially for truck hoods and house-style tents). The lubricant may be a hydrocarbon type (low molecular weight polyethylene, paraffin), a fatty acid type (stearic acid, hydroxystearic acid, complex stearic acid, oleic acid), aliphatic alcohol type, aliphatic amide type (stearamide, oxystearamide, oleylamide, erucylamide, ricinoleamide, behenamide, methylolamide, methylene bisstearamide, methylene bisstearbehenamide, bisamic acid of higher fatty acid, stearamide, complex amide), aliphatic ester type (n-butyl stearate, methylhydroxystearate, polyhydric alcohol fatty acid ester, saturated fatty acid ester, ester wax), fatty acid metal soap type, etc., which may be used alone or in combination. In order to improve the abrasion resistance of the soft polyvinyl chloride resin-impregnated coating layer and extend its service life, it is preferable to include 0.05 to 5% by mass of spherical silicone fine powder relative to the soft polyvinyl chloride resin-impregnated coating layer. The spherical silicone microparticles are preferably one or more selected from silicone rubber powder, silicone resin powder, hydrophobized silica powder, grafted silicone powder, and composite powder in which the surface of silicone rubber particles is coated with silicone resin. The silicone rubber powder is a spherical fine powder (average particle size 5 to 13 μm) or irregular particles (average particle size 25 to 140 μm) of silicone rubber crosslinked with linear dimethylpolysiloxane, and the silicone resin powder is a spherical fine powder (average particle size 5 to 13 μm) or irregular particles (average particle size 25 to 140 μm) in which the siloxane bond is (RSiO 3 / 2The hydrophobic silica powder is spherical particles (average particle diameter 0.8-3.5 μm) of spherical amorphous silica whose surface is hydrophobized with silicone. The grafted silicone powder is spherical particles (average particle diameter 20-30 μm, silicone content 70-90% by mass) of graft polymer in which acrylic side chains or vinyl acetate side chains are introduced to linear organopolysiloxane. The composite powder in which the surface of silicone rubber particles is coated with silicone resin is spherical fine powder of silicone rubber crosslinked with linear dimethylpolysiloxane whose surface is hydrophobized with siloxane bonds (RSiO 3 / 2 The particles are spherical composite particles (average particle diameter: 5 to 12 μm) coated with a cured polyorganosilsesquioxane crosslinked in a three-dimensional network, represented by n.
[0025] The reactive liquid synthetic rubber is one or more selected from butadiene rubber, isoprene rubber, and farnesene rubber, and is used in the range of 5 to 30 parts by mass per 100 parts by mass of vinyl chloride resin. The reactive liquid synthetic rubber is compatible with the plasticizer contained in the soft vinyl chloride resin composition, and penetrates into the vinyl chloride resin fine particles together with the plasticizer to become a softener for the vinyl chloride resin. In this state, the soft vinyl chloride resin composition is heated and gelled to form a soft vinyl chloride resin impregnated coating layer. In the soft vinyl chloride resin impregnated coating layer after coating, the reactive liquid synthetic rubber molecules are entangled with the vinyl chloride resin main chain. Next, the reactive liquid synthetic rubber is cured to enable hybrid formation in which a network of rubber molecular chains is entangled with the vinyl chloride resin main chain throughout the soft vinyl chloride resin impregnated coating layer. The integration of the vinyl chloride resin with the cured liquid rubber makes the soft vinyl chloride resin impregnated coating layer strong, improving resistance to bending, wear, heat and cold.
[0026] The reactive butadiene liquid rubber forms a rubber cured product by having either a -COOH group or a -OH group at the molecular end. The molecular weight Mn is preferably 1000 to 5000, particularly 1300 to 3500, and the viscosity is preferably in the range of 50 to 1000 poise (25°C), particularly 200 to 500 poise (25°C). The reactive butadiene liquid rubber contains 5 to 25% by mass of styrene and / or acrylonitrile as a block copolymerization component, and 10 to 50% by mass of isoprene or hydrogenated isoprene as a copolymerization component. The reactive butadiene liquid rubber has low viscosity and excellent rubber elasticity when rubberized when it has about 75 to 80% of 1,4-cis structure or 1,4-trans structure and about 20 to 25% of 1,2-vinyl structure. This generation ratio is possible by a radical polymerization method. The reactive isoprene liquid rubber preferably has either a -COOH group or a -OH group at the molecular (both) terminals and has a molecular weight Mn in the range of 3000 to 25000. The reactive isoprene liquid rubber contains 5 to 25 mass% of styrene and / or acrylonitrile as a block copolymerization component, and 10 to 50 mass% of butadiene or hydrogenated isoprene as a copolymerization component. Examples of reactive farnesene rubber include rubbers containing α-farnesene ((3E,7E)-3,7,11-trimethyl-1,3,6,10-dodecatetraene) and β-farnesene (7,11-dimethyl-3-methylene-1,6,10-dodecatriene) as monomers, copolymer rubbers of farnesene and styrene, and copolymer rubbers of farnesene and butadiene. The reactive Funnelsen-based liquid rubber preferably has either a -COOH group or a -OH group at the molecular (both) terminals and has a molecular weight Mn in the range of 3000 to 50000. The cured products of these reactive liquid synthetic rubbers are formed by dehydration condensation of the -COOH group and the -OH group at the molecular (both) terminals, but can also be formed by addition reaction with crosslinking agents such as diamines, polyamines, diisocyanates, polyisocyanates, epoxy-amines, aziridines, and oxazolines, or condensation reaction with compounds such as diols, polyols, dicarboxylic acids, and polycarboxylic acids.
[0027] Furthermore, a rubber cured product in which part of the liquid rubber cured product is bonded to silica particles can also be used. By reacting with the silanol groups (Si-OH groups) on the surface of the silica particles and becoming part of the liquid rubber cured product, the liquid rubber cured product becomes tougher, improving its flexural durability (resistance to flapping) and abrasion resistance, and also improving the cold resistance and heat resistance (softening temperature) of the soft polyvinyl chloride resin impregnated coating layer. This improved heat resistance not only improves the peel strength of the joint when industrial canvases are joined together with a heat-sealed lap, but also improves the durability of the joint under the hot sun (resistance to peeling of the sewn parts). Silica particles are used in an amount of 1 to 25% by weight with respect to the reactive liquid synthetic rubber, and are incorporated as part of the rubber hardened product by forming (dehydration condensation) chemical bonds between the silanol groups (Si-OH groups) on the silica surface and the -COOH and -OH groups at the molecular (both) ends of the reactive liquid synthetic rubber, so that the silica particles are contained in an amount of 0.05 to 2.5% by mass with respect to the soft polyvinyl chloride resin impregnated coating layer. Furthermore, by adding a crosslinking agent such as diamine, polyamine, diisocyanate, polyisocyanate, epoxy-amine, aziridine, oxazoline, or by interposing a compound such as diol, polyol, dicarboxylic acid, polycarboxylic acid, the molecular chain can be lengthened to improve the flexibility and toughness of the rubber hardened product. The generation of such a rubber hardened product is carried out simultaneously with the gelation heat treatment of the soft polyvinyl chloride resin paste that forms the soft polyvinyl chloride resin impregnated coating layer, and a homogeneous rubber hardened product is formed throughout the soft polyvinyl chloride resin impregnated coating layer. The soft polyvinyl chloride resin paste composition may contain a silane coupling agent to assist the chemical bonding between the liquid synthetic rubber and the silica.
[0028] Silica has a BET specific surface area of 100 to 300 m 2Synthetic amorphous silica having a particle size of 1 to 40 μm or less is preferred. Synthetic amorphous silica may be either wet-process silica (precipitation method or gel method) or dry-process silica (fumed silica). The surface of the silica has silanol (Si-OH group), and the silanol group reacts with -COOH group, -OH group, etc. at the molecular (both) ends of reactive liquid synthetic rubber, and the silica particles become part of the rubber component. In particular, this reaction is subjected to an addition reaction with a crosslinking agent such as diamine, polyamine, diisocyanate, polyisocyanate, epoxy-amine, aziridine, oxazoline, or a compound such as diol, polyol, dicarboxylic acid, polycarboxylic acid, etc., to toughen the rubber cured product, improving its bending durability (flutter resistance) and abrasion resistance, and also improving the cold resistance and heat resistance (softening temperature) of the soft vinyl chloride resin impregnated coating layer. This improved heat resistance is not only improved in peel strength at the joint where industrial canvases are heat-sealed and lap-bonded, but also manifests itself as peel resistance at surface temperatures of 40 to 60°C under the blazing sun. Functional groups such as amino groups, vinyl groups, epoxy groups, methacryl groups, acrylic groups, chlorine groups, mercapto groups, isocyanurate groups, and isocyanate groups may be introduced onto the silica surface. The silica particles are preferably surface-modified particles treated with a silane coupling agent. Silane coupling agents are alkoxysilane compounds having two or more different reactive groups in the molecule represented by the general formula: XR-Si(Y)3, for example, X=amino group (aminosilane), vinyl group (vinylsilane), epoxy group (epoxysilane), methacryl group (methacrylsilane), acrylic group (acrylicsilane), chloro group (chlorosilane), mercapto group (mercaptosilane), isocyanurate group (isocyanuratesilane), isocyanate group (isocyanatesilane), etc. (R=alkyl chain), Y=methoxy group, ethoxy group, etc. Surface modification of silica is -Si-R-Si(Y)3 modification of the silanol group of silica, but it may also be (-O)3Si-RX modification of the siloxane bond part of silica.
[0029] The manufacturing method of canvas for industrial materials of the present invention, in which a soft vinyl chloride resin-impregnated coating layer is formed on the entire surface of a fabric containing multifilament yarns and staple spun yarns in a regularly alternating arrangement, is characterized by comprising the following steps: 1) preparing a soft vinyl chloride resin composition containing at least three types of vinyl chloride resin, plasticizer, and reactive liquid synthetic rubber (one or more selected from butadiene-based, isoprene-based, and farnesene-based), 2) applying the soft vinyl chloride resin composition to the fabric to form a soft vinyl chloride resin-impregnated coating layer, and 3) converting the reactive liquid synthetic rubber into a cured rubber product to impregnate the entire soft vinyl chloride resin-impregnated coating layer with synthetic rubber. The application of the soft vinyl chloride resin composition (paste sol) to the fabric and the formation of the soft vinyl chloride resin impregnated coating layer can be carried out by dipping (immersion-impregnation-roll squeezing-heat treatment gelation of the paste sol) or coating (impregnation coating-heat treatment gelation of the paste sol) such as gravure coating method, comma coating method, roll coating method, reverse roll coating method, bar coating method, doctor knife coating method, etc. To convert the reactive liquid synthetic rubber into a rubber cured product, a crosslinking agent such as diamine, triamine, tetramine, polyamine, diisocyanate (e.g., hexamethylene diisocyanate: HMDI), triisocyanate (e.g., isocyanurate by trimer of HMDI), polyisocyanate, epoxy-amine, aziridine, oxazoline, etc., especially a crosslinking agent with 3 or 4 functional groups, is used to make a dense and complex rubber cured product. The conversion of the reactive liquid synthetic rubber into a rubber cured product is carried out simultaneously with the gelation of the soft vinyl chloride resin composition, so that a homogeneous rubber cured product is formed throughout the soft vinyl chloride resin impregnated coating layer. The reaction between the reactive liquid synthetic rubber and the crosslinking agent is preferably an equimolar reaction, but excess liquid synthetic rubber may remain in the soft vinyl chloride resin impregnated coating layer. The remaining reactive liquid synthetic rubber is compatible with the plasticizer and acts to lower the glass transition temperature of the soft vinyl chloride resin impregnated coating layer, that is, as a cold resistance imparting agent. The remaining reactive liquid synthetic rubber is 1 to 10 parts by mass per 100 parts by mass of the vinyl chloride resin.
[0030] The soft polyvinyl chloride resin impregnated coating layer is 200 to 400 g / m 2The lower the weight, the lighter the canvas will be, and the higher the weight, the stronger and more durable it will be. Conventional canvas for industrial materials is No. 2 (approx. 410 g / m 2 ), No. 3 (approximately 340g / m 2 ), No. 4 (approximately 280g / m 2 ), No. 5 (approximately 250g / m 2 ), No. 6 (approximately 200g / m 2 ) and No. 7 (approx. 170g / m 2 ) fabric as the base fabric, with a soft vinyl chloride resin impregnated coating layer, and No. 2 canvas (approx. 750 g / m 2 ), No. 3 canvas (approx. 640g / m 2 ), No. 4 canvas (approx. 560g / m 2 ), No. 5 canvas (approx. 530g / m 2 ), No. 6 canvas (approx. 470g / m 2 ), No. 7 canvas (approx. 430g / m 2 However, in the case of the canvas for industrial materials of the present invention, even if a fabric one rank lighter is used, sufficient tear strength can be obtained, for example, about 530 g / m 2 No. 4 canvas, approx. 470g / m 2 No. 5 canvas, approx. 430g / m 2 No. 6 canvas, approx. 390g / m 2 This makes it possible to make the canvas one level lighter, similar to No. 7 canvas.
[0031] The canvas for industrial materials of the present invention may also be provided with an antifouling layer, which may be, for example, a transparent layer made of an acrylic resin, a fluorine-based copolymer resin, an acrylic-silicone copolymer resin, an acrylic-fluorine copolymer resin, an acrylic-urethane copolymer resin, a blend of an acrylic resin and a fluorine-based copolymer resin, or a layer containing silica particles, colloidal silica, an organosilicate, a silane coupling agent, an ultraviolet absorber (benzophenone tautomer, benzotriazole tautomer, triazine tautomer, etc.) in these resins. These antifouling layers are formed by applying and drying these coating materials using gravure coating, or by laminating a fluorine-containing resin film or a multilayer film such as a fluorine-containing resin / acrylic resin layer with an adhesive or by thermal melting. In addition, a photocatalytic layer containing a photocatalytic inorganic material (for example, photocatalytic titanium oxide, photocatalytic tungsten oxide, etc.) on these antifouling layers may also be provided.
[0032] The manufacturing process of the canvas for industrial materials of the present invention may include a step of applying surface decorative embossing. Surface decorative embossing can be performed by known embossing methods, such as glossing with a mirror roll, matte finish with a matte finish roll, and design with a pattern roll. In particular, it is preferable to apply an identification mark of the manufacturer's name (e.g., "HIRAOKA"), logo mark, or product name (e.g., "ULTRA MAX") at specific intervals (e.g., every 100 cm) to the end or specific parts of the canvas for industrial materials. Such identification markings include a design in which the entire canvas is matte embossed and only the identification marking part is mirror embossed, or a design in which the entire canvas is mirror embossed and only the identification marking part is matte embossed, or an embossing in which the identification marking part is recessed, and these markings make it easy to distinguish from similar products of other companies. The embossing is performed by pressing an embossing roll set at 100 to 180°C with a pair of rubber rolls, and the embossing is fixed by cooling (air-cooled and water-cooled rolls) after embossing.
[0033] The present invention will now be described in more detail with reference to examples and comparative examples, but the present invention is not limited to the scope of these examples. The test methods used in the examples and comparative examples of the present invention are as follows. (1) Appearance quality (balance between glossy and diffusely reflective areas) 1: Good 2: Not very good 3: Not good (2) Tear strength (JIS L1096 trapezoid method) balance Warp tear strength (kgf) / weft tear strength (kgf) 1: 0.8~1.25 2: 0.7~0.79 or 1.26~1.43 3: 0.5~0.69 or 1.44~2.0 4: Other than the above (3) Scott type reciprocating bending abrasion test (JIS L1096 8.19.2 B method) A) Test pieces measuring 25mm wide x 120mm long were taken from the canvas and left to stand in a 25℃ environment for 24 hours. They were then attached to a Scott-type testing machine and subjected to 1,000 and 3,000 reciprocating flexions with a load of 1kgf in a constant temperature room at 25℃. The surface condition after the test was observed and the dynamic cold resistance was evaluated as follows: 1: Minor wear is observed 2: Wear marks are observed on the soft polyvinyl chloride resin impregnated coating layer, but there is no problem. 3: The soft polyvinyl chloride resin impregnated coating layer peels off or wears away, exposing the fabric (Less than 10%) 4: The soft polyvinyl chloride resin impregnated coating layer peels off or wears away, exposing the fabric Accept (more than 10%) B) Test pieces measuring 25mm wide x 120mm long were taken from the canvas and left to stand in a -10°C environment for 24 hours. They were then attached to a Scott-type testing machine and subjected to 100 and 300 reciprocating flexing cycles with a load of 1kgf in a constant temperature room at -10°C. The surface condition after the test was observed and the dynamic cold resistance was evaluated as follows: 1: No abnormality is detected 2: Minor cracks observed in the soft polyvinyl chloride resin impregnated coating layer 3: Partial peeling or falling off of the soft polyvinyl chloride resin impregnated coating layer, or cracks are observed (4) Dematcha repeated bending fatigue durability test (JIS K6301 compliant) A 50mm wide x 150mm long sample was taken from the canvas and left to rest in a -10℃ environment for 24 hours, after which it was folded in half top and bottom from the 25mm centre of the width to create a 25mm wide x 150mm long folded test piece. This was then attached to a YSS Dematcha Flexing Tester (manufactured by Yasuda Seiki Mfg. Co., Ltd.) and a simulated test of repeatedly folding and unfolding the test piece was carried out 100 and 300 times in a constant temperature room at -10℃, and the surface condition of the test piece was observed to determine the dynamic cold resistance as follows. 1: No abnormality is detected 2: Minor cracks observed in the soft polyvinyl chloride resin impregnated coating layer 3: Partial peeling or falling off of the soft polyvinyl chloride resin impregnated coating layer is observed. (5) Heat resistance creep test of joints (heat resistance test) The ends of the two pieces of canvas in the weft direction were overlapped in a straight line with a width of 8 cm, and the soft polyvinyl chloride resin impregnated coating layer was melted by oscillation at an anode current of 1.0 A using a high-frequency welder (YAMAMOTO VINITA Co., Ltd. YTO-8A type: high-frequency output 8KW) equipped with a 4 cm wide x 30 cm long weld bar (flat blade) to obtain a canvas joint. A test piece of 3 cm wide x 30 cm long (warp direction) was taken from this joint, overlapping the fused joint and including a width of 8 cm in the warp direction, and used as a creep resistance test piece. The heat creep resistance in the warp direction was evaluated using a creep tester (TOYO SEIKI SEISAKUSHO Co., Ltd.: 100LDR type) under conditions of 25°C x 24 hours and load conditions of 50 kgf, 60 kgf, and 70 kgf. Similarly, a test piece in the weft direction was prepared and the heat creep resistance in the weft direction was evaluated. Evaluation criteria 1: After 24 hours, some stretching was observed at the joint (Excellent) 2: The joint broke and the test piece broke apart within 12 to 24 hours (good). 3: The joint broke and the test piece broke apart within 1 to 12 hours (poor) 4: The joint broke and the test piece broke apart within 1 hour (failure)
[0034] Example 1 <Fabric (1)> The warp and weft yarns are made of multifilament yarns (M) and staple spun yarns (S) in an "MMSS" alternating arrangement (four repeat units), with a warp yarn pick density of 40 threads / inch and a weft yarn pick density of 37 threads / inch, woven in a plain weave, with a void ratio of 7% and a mass of 215g / m 2 The fabric used was: *Multifilament yarn (M) is a 500 denier (555 dtex) polyester multifilament yarn (96 filaments: 200 twists / m) * Staple fiber spun yarn (S) is a 20-count (590 dtex) polyester staple fiber spun yarn (S twist: 400 twists / m). The fabric was treated for water repellency (dipping, heat treatment) with an acrylate / vinyl chloride resin copolymer emulsion (solid content 5% by mass) having a perfluoroalkyl group with 6 carbon atoms to prevent rainwater penetration (water absorption) in the event that an abnormality occurs in the soft vinyl chloride resin impregnated coating layer. This was designated fabric (1). <Soft polyvinyl chloride resin impregnated coating layer> A processing liquid was prepared based on a vinyl chloride resin composition paste (vinyl chloride resin, plasticizer, reactive butadiene liquid rubber) for forming a soft vinyl chloride resin-impregnated coating layer of the following <Composition 1>. Next, the fabric (1) was dipped (immersed) in a liquid bath filled with this processing liquid, and the processing liquid of <Composition 1> was impregnated into the fabric (1) at normal pressure. The fabric (1) was then pulled out of the liquid bath and simultaneously squeezed with a rubber mangle roll to remove excess processing liquid, forming a soft vinyl chloride resin-impregnated coating layer. Next, a gelation heat treatment was performed for 3 minutes in a hot air oven at 180°C to form a soft vinyl chloride resin-impregnated coating layer of 290 g / m 2 is formed on the entire surface of the fabric (1), with a mass of 505 g / m 2 This gelling heat treatment converts the polyvinyl chloride resin composition paste into soft polyvinyl chloride resin and simultaneously converts the reactive butadiene-based liquid rubber into hardened rubber, forming a polymer alloy in which the molecular chains of the hardened rubber are entangled with the polyvinyl chloride resin main chain throughout the entire area of the soft polyvinyl chloride resin-impregnated coating layer obtained. <Formulation 1> Processing fluid for forming soft polyvinyl chloride resin impregnated coating layer Paste polyvinyl chloride resin (degree of polymerization 1700) 100 parts by weight Diisononyl phthalate (DINP plasticizer) 60 parts by weight Reactive butadiene liquid rubber* 10 parts by mass Isocyanurate (HMDI* trimer: NCO crosslinking agent) 2 parts by weight Chlorinated paraffin (flame retardant and plasticizer) 5 parts by weight Epoxidized soybean oil (stabilizer and plasticizer) 4 parts by weight Antimony trioxide (flame retardant) 20 parts by weight Zinc stearate (stabilizer) 2 parts by weight UV absorber (triazine tautomer) 0.5 parts by weight Titanium oxide (white pigment) 1 part by weight Phthalocyanine green (green pigment) 3 parts by weight Carbon black (black pigment) 0.5 parts by weight Behenamide (lubricant) 1 part by weight Trichloroethylene (dilution solvent) 20 parts by weight *Butadiene liquid rubber: Contains 15% by mass of styrene as a block copolymer component. Properties: Average molecular weight 3000 with -COOH groups at both ends of the molecule *HMDI: Hexamethylene diisocyanate HMDI trimer (isocyanurate) has three isocyanate groups
[0035] Example 2 The fabric (1) in Example 1 was changed to fabric (2) and blend 1 was changed to blend 2, but the same as in Example 1 was used. The mass was 505 g / m 2 Obtained Canvas (2). In <Mixture 2>, 10 parts by mass of the reactive butadiene-based liquid rubber in <Mixture 1> is replaced with 10 parts by mass of reactive isoprene-based liquid rubber. The reactive isoprene-based liquid rubber contains 10% by mass of acrylonitrile as a block copolymer component, has -COOH groups at both ends of the molecule, and has an average molecular weight of 2,500. <Fabric (2)> The warp yarn group is made of multifilament yarn (M) and staple spun yarn (S) in an "MMMSS" alternating arrangement (repeat unit of 5), with a warp yarn pick density of 40 yarns / inch, the weft yarn group is made of multifilament yarn (M) and staple spun yarn (S) in an "MMSSS" alternating arrangement (repeat unit of 5), with a weft pick density of 37 yarns / inch, and woven in a plain weave with a void ratio of 7% and a mass of 215g / m 2 The fabric (water-repellent treatment was the same as in Example 1) was used. *Multifilament yarn (M) is a 500 denier (555 dtex) polyester multifilament yarn (96 filaments: 200 twists / m) * Staple fiber spun yarn (S) is a 20-count (590 dtex) polyester staple fiber spun yarn (S twist: 400 twists / m).
[0036] Example 3 The fabric (1) in Example 1 was changed to fabric (3), and blend 1 was changed to blend 3, but the same as in Example 1, with a mass of 518 g / m 2 Obtained Canvas (3). In <Mixture 3>, 10 parts by mass of the reactive butadiene-based liquid rubber in <Mixture 1> is replaced with 10 parts by mass of reactive β-Funnelsen-based liquid rubber. The reactive β-Funnelsen-based liquid rubber contains 10% by mass of butadiene as a block copolymer component, has -COOH groups at both ends of the molecule, and has an average molecular weight of 5,000. <Fabric (3)> The warp and weft yarns are arranged in an "MMS" alternating arrangement (3 repeat units) of multifilament yarns (M) and staple spun yarns (S). The warp yarn density is 44 threads / inch, the weft yarn density is 40 threads / inch, and the fabric is woven in a plain weave with a void ratio of 8% and a mass of 228g / m. 2 The fabric (water-repellent treatment was the same as in Example 1) was used. *Multifilament yarn (M) is a 500 denier (555 dtex) polyester multifilament yarn (96 filaments: 200 twists / m) * Staple fiber spun yarn (S) is a 14-count two-ply (844 dtex) polyester staple fiber spun yarn (S twist: 400 twists / m) with a larger fineness (dtex) than multifilament yarn (M). This is indicated as (S) in Table 1.
[0037] Example 4 The fabric (1) in Example 1 was changed to fabric (4), and the fabric was the same as Example 1, with a mass of 523 g / m 2 Obtained Canvas (4). <Fabric (4)> The warp and weft yarns are arranged in an "MSS" alternating arrangement (3 repeat units) of multifilament yarns (M) and staple spun yarns (S). The warp yarn density is 44 threads / inch, the weft yarn density is 40 threads / inch, and the plain weave has a void ratio of 7% and a mass of 233g / m. 2 The fabric (water-repellent treatment was the same as in Example 1) was used. *Multifilament yarn (M) is a 1000 denier (1111 dtex) polyester multifilament yarn (192 filaments: 200 twists / m) with a larger fineness (dtex) than staple spun yarn (S). This is indicated as (M) in Table 1. * Staple fiber spun yarn (S) is a 20-count (590 dtex) polyester staple fiber spun yarn (S twist: 400 twists / m).
[0038] Example 5 The fabric (1) in Example 1 was changed to fabric (5), and blend 1 was changed to blend 2, but the same as in Example 1, with a mass of 538 g / m 2 Obtained Canvas (5). <Fabric (5)> The warp and weft yarns are arranged in an alternating "MMSSS" pattern (5 repeat units), with a warp thread density of 40 threads / inch and a weft thread density of 37 threads / inch, and woven in a plain weave with a void ratio of 8% and a mass of 238g / m. 2 The fabric (water-repellent treatment was the same as in Example 1) was used. *Multifilament yarn (M) is a 1000 denier (1111 dtex) taslan-processed yarn made of polyester fiber (192 filaments: 200 twists / m) with the filaments loosely entangled with each other and S-twisted at 10 T / m; this is indicated as "light black M" in Table 1. * Staple fiber spun yarn (S) is a 20-count (590 dtex) polyester staple fiber spun yarn (S twist: 400 twists / m).
[0039] Example 6 The fabric (1) in Example 1 was changed to fabric (6), and blend 1 was changed to blend 3, but the same as in Example 1, with a mass of 525 g / m 2 of Canvas (6). <Fabric (6)> The warp and weft yarns are arranged in an alternating "MMSS" pattern (four repeat units), with a warp thread density of 38 threads / inch and a weft thread density of 34 threads / inch, and woven in a plain weave. The void ratio is 8%, and the mass is 220g / m. 2 The fabric (water-repellent treatment was the same as in Example 1) was used. *Multifilament yarn (M) is a core-sheath spun yarn in which a polyester multifilament long fiber yarn of 750 denier (833 dtex: twist number 200 times / m) is used as the core, and the entire circumference is covered with 1.4 denier (1.56 dtex) polyester staple fiber of 100 mm length in a core / sheath weight ratio of 65 / 35, and this is represented as "light black M" in Table 2. * Staple fiber spun yarn (S) is a 20-count (590 dtex) polyester staple fiber spun yarn (S twist: 400 twists / m).
[0040] Example 7 The fabric (1) in Example 1 was changed to fabric (7), but the fabric was the same as Example 1, with a mass of 532 g / m 2 of Canvas (7). <Fabric (7)> The warp and weft yarns are arranged in an alternating "MMMSSS" pattern (repeated 6 threads), with a warp thread density of 40 threads / inch and a weft thread density of 37 threads / inch, woven in a plain weave, with a void ratio of 8% and a mass of 227g / m. 2 The fabric (water-repellent treatment was the same as in Example 1) was used. *Multifilament yarn (M) consists of two 500 denier (555 dtex) polyester multifilament yarns (96 filaments: 200 twists / m), with a 500 denier (555 dtex) fully aromatic polyamide fiber (300 filaments: polyparaphenylene terephthalamide) multifilament yarn in the middle (in Table 2, this is indicated by a capital M). * Staple fiber spun yarn (S) is a 20-count (590 dtex) polyester staple fiber spun yarn (S twist: 400 twists / m).
[0041] Example 8 The fabric (1) in Example 1 was changed to fabric (8), but the fabric was the same as Example 1, with a mass of 536 g / m 2 The result was Canvas (8). <Fabric (8)> The warp and weft yarns are arranged in an alternating "MS" arrangement (2 repeat units) of multifilament yarns (M) and staple spun yarns (S). The warp yarn density is 40 threads / inch, the weft yarn density is 37 threads / inch, and the fabric is woven in a plain weave with a void ratio of 8% and a mass of 236g / m. 2 The fabric (water-repellent treatment was the same as in Example 1) was used. * Multifilament yarn (M) is a multifilament yarn made of 500 denier (555 dtex: twist count 200 times / m) fully aromatic polyamide fiber (filament count 300: polyparaphenylene terephthalamide) (in Table 2, it is indicated by a capital M). * Staple fiber spun yarn (S) is a 20-count two-ply (590 dtex) fully aromatic polyamide fiber (polyparaphenylene terephthalamide) staple fiber spun yarn (S twist: 400 twists / m). In Table 2, it is indicated with a capital M.
[0042] Example 9 The machining fluid was changed from Blend 1 to Blend 4, but the machining fluid was the same as in Example 1. The mass was 505 g / m 2 of Canvas (9). The processing fluid of Blend 4 is prepared by adding 2 parts by mass of surface-modified silica particles to the processing fluid of Blend 1. The surface-modified silica particles are dry silica (gel method: average particle diameter 2 μm, BET specific surface area 300 m 2 / g) in a 5% by mass aqueous solution of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane (a silane coupling agent) was stirred at 24°C for 3 hours, then separated and dried; it contains a mixture of -Si-R-Si(OCH3)3 modifications that bond to the silanol groups of the silica and (-O)3Si-R-NH2 modifications that bond to the siloxane moieties.
[0043] Example 10 The surface of the canvas (1) of Example 1 was coated with the fluororesin paint of [Blend 5] below using a 100 mesh gravure roll, and then heated and dried in a hot air oven at 120°C for 2 minutes to harden the fluororesin paint of [Blend 5] to form an antifouling coating film layer (4 g / m 2 ) and weighs 509g / m 2 Obtained Canvas (10). [Formulation 5] Fluorine-based resin paint (for forming anti-fouling layer) Hydroxyl-containing fluoroolefin vinyl ether copolymer (fluorine-based resin) 100 parts by mass Isocyanurate trimer of hexamethylene diisocyanate (isocyanate) 10 parts by mass Colloidal silica (antistatic) 8 parts by weight Triazine tautomer (ultraviolet absorber) 5 parts by weight Curing catalyst: Dibutyltin dilaurate (approximately 10 ppm for fluororesin) Toluene / butyl acetate (diluent with a mass ratio of 1:1) 400 parts by mass
[0044] [Table 1]
[0045]
Table 2
[0046] In the canvases (1) to (10) of Examples 1 to 10, the multifilament yarns and the staple spun yarns are regularly alternately arranged, and the number of repeating units in the alternate arrangement is 2 to 6, and the alternate arrangement is either a combination of multifilament yarns (1 to 3) and staple spun yarns (1 to 3) (Tables 1 and 2). As a result, the tear strength balance in the warp and weft directions is excellent, and the adhesion between the fabric and the soft polyvinyl chloride resin-impregnated coating layer is strengthened and stabilized, so that the bending durability (flutter resistance) is excellent, and all of the appearances (balance between glossy parts and diffuse reflection parts) are good. In particular, the soft polyvinyl chloride resin-impregnated coating layer is compounded with a synthetic rubber cured product, and the formation of the synthetic rubber cured product is a special one in which a soft polyvinyl chloride resin composition containing a reactive liquid synthetic rubber is applied to the fabric, and then the reactive liquid synthetic rubber is converted into a rubber cured product, and the synthetic rubber cured product is compounded over the entire area of the soft polyvinyl chloride resin-impregnated coating layer. In the soft polyvinyl chloride resin-impregnated coating layer immediately after coating, the molecular chains of reactive liquid rubber are present in a state entangled with the polyvinyl chloride resin main chain, and in the next process, by hardening the reactive liquid synthetic rubber, the molecular chains of the rubber structure are spread throughout the entire soft polyvinyl chloride resin-impregnated coating layer, and by constructing a network that is particularly entangled with the polyvinyl chloride resin main chain, it is possible to obtain an industrial canvas that is excellent in flexural durability (flutter resistance), especially flexural durability below freezing (Scott flexural abrasion test, De Mattia flexural fatigue test) and heat resistance under the hot sun (joint heat creep test). In this embodiment, even if the soft polyvinyl chloride resin-impregnated coating layer is designed to be thinner than conventional products to reduce the weight of the canvas, it is possible to obtain durability equivalent to that of conventional products. In particular, the canvas (9) of Example 9 has a structure in which the reactive liquid synthetic rubber bonds (through a crosslinking agent) with the silanol groups (Si-OH groups) on the surface of the silica particles, and the structure of the cured rubber contains silica (treated with a silane coupling agent) at the intermediate point, which toughens the cured rubber and further improves its flexural durability (De Mattia flexural fatigue test) and abrasion resistance (Scott flexural abrasion test), as well as the cold resistance and heat resistance (bonding heat creep test) of the soft polyvinyl chloride resin-impregnated coating layer. In this embodiment, even if the soft polyvinyl chloride resin-impregnated coating layer is designed to be thinner than conventional products to reduce the weight of the canvas, it is possible to obtain the same durability as conventional products.The canvas (10) of Example 10 had a fluorine-based resin antifouling coating layer formed on the surface of the canvas (1) of Example 1, which made it easy to clean and wipe off soot and dust stains that adhere and accumulate during outdoor use. The combined use of staple spun yarn and Taslan bulky yarn (long fiber) in the fabric (5) of Example 5 and the combined use of staple spun yarn and core spun sheath yarn (long fiber core) in the fabric (6) of Example 6 both provided anchor parts comparable to the fluff of the staple fibers, making it possible to simultaneously improve bending durability (resistance to flapping) while maintaining tear strength.
[0047] [Comparative Example 1] The machining fluid was changed from Blend 1 to Blend 6 in Example 1. The machining fluid was the same as in Example 1, with a mass of 503 g / m 2 I got canvas(11). The processing liquid of <Mixture 6> is a compound obtained by omitting 10 parts by mass of the reactive butadiene-based liquid rubber (having -COOH groups at both ends of the molecule and an average molecular weight of 3,000) and 2 parts by mass of isocyanurate (HMDI trimer: NCO crosslinking agent). The appearance quality of the comparative canvas (11) was good, but compared to the canvas (1) of Example 1, it was clearly inferior in bending durability below freezing (Scott bending abrasion test and De Mattia bending fatigue test) and heat resistance under the hot sun (heat creep test of joints), due to the lack of a rubber structure throughout the soft polyvinyl chloride resin impregnated coating layer.
[0048] [Comparative Example 2] The machining fluid was changed from Blend 1 to Blend 7 in Example 1. The machining fluid was the same as in Example 1, with a mass of 503 g / m 2 of Canvas (12). The processing fluid of <Mixture 7> is a compound in which 10 parts by mass of the reactive butadiene-based liquid rubber (having -COOH groups at both molecular ends and an average molecular weight of 3000) of <Mixture 1> is replaced with 10 parts by mass of butadiene-based liquid rubber having an average molecular weight of 3000 and no functional groups at both molecular ends, and 2 parts by mass of isocyanurate (HMDI trimer: NCO crosslinking agent) is omitted. The butadiene-based liquid rubber having no functional groups remained in a liquid state within the soft polyvinyl chloride resin-impregnated coating layer, and exerted the effect of lowering the glass transition temperature of the polyvinyl chloride resin, resulting in superior bending durability (Scott flexure abrasion test / De Mattia flexure fatigue test) below freezing points than the canvas (11) of Comparative Example 1 (similar to the canvas (1) of Example 1). However, conversely, the presence of the butadiene-based liquid rubber had a negative effect on heat resistance (heat creep test for joints), resulting in a result inferior to the canvas (11) of Comparative Example 1.
[0049] [Comparative Example 3] The same as in Example 1 except that the processing fluid of <Composition 1> in Example 1 was changed to the processing fluid of <Composition 8>, and the mass was 505 g / m 2 I got canvas(13). The processing liquid of <Mixture 8> is a compound in which 10 parts by mass of the reactive butadiene liquid rubber (having -COOH groups at both ends of the molecule and an average molecular weight of 3000) of <Mixture 1> is replaced with 10 parts by mass of butadiene rubber powder (registered trademark "Kane Ace" M-711: Kaneka Corporation), and 2 parts by mass of isocyanurate (HMDI trimer: NCO crosslinking agent) is omitted. The butadiene rubber powder (non-crosslinked) was incompatible and dispersed in the soft polyvinyl chloride resin impregnated coating layer, and due to the cold resistance of the butadiene rubber itself, the flexural durability (Scott flexural abrasion test / De Mattia flexural fatigue test) at sub-zero temperatures was slightly better than the canvas (11) of Comparative Example 1 (not as good as the canvas (1) of Example 1), but numerous cracks occurred due to the influence of the incompatible dispersion. Also, with regard to heat resistance (heat creep test of joints), no particular improvement was observed compared to the canvas (11) of Comparative Example 1.
[0050] [Table 3]
[0051] [Comparative Example 4] The fabric (1) in Example 1 was changed to fabric (9), and the fabric was the same as Example 1, with a mass of 445 g / m 2 The result was canvas (14). <Fabric (9)> Both the warp and weft yarns are multifilament yarns, and the fabric is woven in a plain weave with a warp density of 28 threads / inch and a weft density of 24 threads / inch. The fabric has a void ratio of 10% and a mass of 165g / m 2 The fabric used was filament woven fabric. *The multifilament yarn is a 500 denier (555 dtex) polyester multifilament yarn (96 filaments: 200 twists / m). This fabric was treated to prevent rainwater penetration (water absorption) in the same manner as in Example 1, and the result was designated fabric (9). The resulting canvas (14) had an excellent balance of tear strength and warp and weft tear strength due to the use of multifilament yarns for both the warp and weft yarns, but the surface of the fabric (9) was smooth, and the adhesion to the soft polyvinyl chloride resin-impregnated coating layer was poor, so that the soft polyvinyl chloride resin-impregnated coating layer peeled off from the fabric (9) in the bending durability test (Scott bending abrasion test and De Mattia bending fatigue test) below freezing point. Also, in the heat resistance test (heat creep test for joints), failure occurred due to thread pull-out.
[0052] [Comparative Example 5] The fabric (1) in Example 1 was changed to fabric (10), and the fabric was the same as Example 1, with a mass of 534 g / m 2 of Canvas (15). <Fabric (10)> Both the warp and weft yarns are made of staple spun yarns, and the warp yarn density is 46 threads / inch and the weft density is 42 threads / inch. The fabric is woven in a plain weave, with a void ratio of 6% and a mass of 235g / m 2 Fabric was used. * Staple fiber spun yarn is 20-count two-ply (590 dtex) polyester staple fiber spun yarn (S twist: 400 twists / m). This fabric was treated to prevent rainwater penetration (water absorption) in the same manner as in Example 1, and the result was designated fabric (10). The resulting canvas (15) had an excellent balance of warp and weft tear strength due to the use of short fiber spun yarns for both the warp and weft groups, but the tear strength was weak. However, the surface of the fabric (10) was uneven with many naps, which increased the adhesion to the soft polyvinyl chloride resin impregnated coating layer, and the flexural durability below freezing (Scott flexural abrasion test and De Mattia flexural fatigue test) and heat resistance (bonding heat creep test) were equivalent to those of the canvas (1) in Example 1.
[0053] [Comparative Example 6] The fabric (1) in Example 1 was changed to fabric (11), but the fabric was the same as Example 1, with a mass of 500 g / m 2 The result was canvas (16). <Fabric (11)> The fabric is woven in a plain weave using multifilament yarns for the warp thread group and staple spun yarns for the weft thread group, with a warp thread pick density of 28 threads / inch and a weft thread pick density of 38 threads / inch. The void ratio is 8%, and the mass is 223g / m 2 Fabric was used. *The multifilament yarn is a 500 denier (555 dtex) polyester multifilament yarn (96 filaments: 200 twists / m). * Staple fiber spun yarn is 20-count two-ply (590 dtex) polyester staple fiber spun yarn (S twist: 400 twists / m). This fabric was treated to prevent rainwater penetration (water absorption) in the same manner as in Example 1, and the result was designated fabric (11). The obtained canvas (16) had an extremely poor balance of tear strength in the warp and weft directions due to the use of multifilament yarns in the warp and staple spun yarns in the weft, and the heat resistance (heat creep test at joints) also showed a significant difference in performance in the warp and weft directions, making it unsuitable for practical use. The flexural durability below freezing (Scott flexural abrasion test and De Mattia flexural fatigue test) was intermediate between Comparative Example 4 (Canvas 14) and Comparative Example 5 (Canvas 15).
[0054] [Comparative Example 7] The fabric (1) in Example 1 was changed to fabric (12), and the fabric was the same as Example 1, with a mass of 516 g / m 2I got canvas(17). <Fabric (12)> The warp and weft yarns are arranged in an alternating "MMSSSSSS" pattern (8 repeat units), with a warp thread density of 38 threads / inch and a weft thread density of 35 threads / inch. The void ratio is 7%, and the mass is 222g / m. 2 Fabric was used. *Multifilament yarn (M) is a 500 denier (555 dtex) polyester multifilament yarn (96 filaments: 200 twists / m) * Staple fiber spun yarn (S) is a 20-count (590 dtex) polyester staple fiber spun yarn (S twist: 400 twists / m). This fabric was treated to prevent rainwater penetration (water absorption) in the same manner as in Example 1, and the result was designated fabric (12). The obtained canvas (17) had a poor appearance quality due to the "MMSSSSSS" alternating arrangement (8 repeat units), and its performance was closer to that of Comparative Example 5 (Canvas 15). The presence of M improved the tear strength slightly, but on the other hand, the flexural durability below freezing (Scott flexural abrasion test / De Mattia flexural fatigue test) and heat resistance (heat creep test of joints) were slightly inferior.
[0055] [Comparative Example 8] The fabric (1) in Example 1 was changed to fabric (13), and the mass was 515 g / m. 2 The result was canvas (18). <Fabric (13)> The warp and weft yarns are arranged in a "MMMMMMSS" alternating pattern (8 repeat units) of multifilament yarns (M) and staple spun yarns (S). The warp yarn density is 33 threads / inch and the weft yarn density is 30 threads / inch. The void ratio is 11% and the mass is 174g / m. 2 Fabric was used. *Multifilament yarn (M) is a 500 denier (555 dtex) polyester multifilament yarn (96 filaments: 200 twists / m) * Staple fiber spun yarn (S) is a 20-count (590 dtex) polyester staple fiber spun yarn (S twist: 400 twists / m). This fabric was treated to prevent rainwater penetration (water absorption) in the same manner as in Example 1, and the result was designated fabric (13). The obtained canvas (18) had a poor appearance quality due to the "MMMMMMSS" alternating arrangement (8 repeat units), and its performance was closer to that of Comparative Example 4 (Canvas 14). The presence of S slightly improved the flexural durability below freezing points (Scott flexural abrasion test and De Mattia flexural fatigue test) and heat resistance (heat creep test of joints), but the tear strength was slightly inferior.
[0056] [Table 4] [Industrial Applicability]
[0057] As is clear from the above examples and comparative examples, the present invention provides an industrial canvas that is excellent in balance of warp and weft tear strength and flexural durability (flutter resistance), particularly at sub-zero temperatures and in joint durability under the hot sun (resistance to peeling at sewn parts), and has a good appearance (balance between glossy and diffuse reflection parts), making it suitable for a wide range of uses as the main body material for tent warehouses (simple houses), roofed tents (assembly tents with awnings used for athletic meets, outdoor events, management headquarters, meetings, receptions, etc.), truck hoods, truck bed covers, open-air storage sheets, etc. Furthermore, the present invention provides a canvas that is as durable as conventional products, even if the canvas is made lighter by designing the soft polyvinyl chloride resin-impregnated coating layer to be thinner than conventional products.
Claims
1. A canvas for industrial materials, comprising a soft polyvinyl chloride resin-impregnated coating layer provided on the entire surface of the fabric, the fabric being woven from a group of warp threads and a group of weft threads, with multifilament yarns and staple spun yarns being regularly alternately arranged in both the warp and weft thread groups, with the number of repeating units in this alternating arrangement being 2 to 6, and the alternating arrangement being any one of nine combinations of the multifilament yarns (1 to 3 threads) and the staple spun yarns (1 to 3 threads), the soft polyvinyl chloride resin-impregnated coating layer containing a cured liquid rubber, the cured liquid rubber being a polymer of one or more reactive liquid rubbers selected from butadiene-based, isoprene-based, and farnesene-based, and a composite of the reactive liquid rubber and silica particles, which is a reaction product with silanol groups (Si-OH groups) on the surfaces of the silica particles.
2. The canvas for industrial materials according to claim 1, wherein the soft polyvinyl chloride resin impregnated coating layer contains silicone microparticles, and the silicone microparticles are one or more types selected from silicone rubber powder, silicone resin powder, hydrophobic silica powder, grafted silicone powder, and composite powder in which the surface of silicone rubber particles is coated with silicone resin.
3. A method for producing canvas for industrial materials, comprising the steps of: 1) preparing a soft vinyl chloride resin composition comprising at least three components: polyvinyl chloride resin, a plasticizer, and a reactive liquid synthetic rubber (one or more selected from butadiene-based, isoprene-based, and farnesene-based). 2) applying the soft vinyl chloride resin composition to the fabric to form a soft vinyl chloride resin-impregnated coating layer (before gelation). 3) simultaneously with the gelation heat treatment of the soft vinyl chloride resin composition to form the soft vinyl chloride resin-impregnated coating layer, converting the reactive liquid synthetic rubber into a rubber cured product to impregnate the entire soft vinyl chloride resin-impregnated coating layer with a synthetic rubber component.
4. A manufacturing method for canvas for industrial materials as described in claim 3, wherein the fabric is woven from a warp yarn group and a weft yarn group, both of which are composed of twisted yarns of multifilament yarns / staple fiber spun yarns, and the multifilament yarns are bulky yarns or twisted yarns having a bulky portion on the outer periphery.
5. 4. The method for producing canvas for industrial materials according to claim 3, wherein the soft polyvinyl chloride resin composition is made to contain silica particles and converted into a composite rubber cured product with the silica particles.
Citation Information
Patent Citations
JP1973061171U
JP1976124169U
JP1978056080U
Sheet-shaped material and its manufacture
JP1984103750A
Soft vinyl chloride resin-made industrial material sheet
JP2015205428A
Cited By
Tear-resistant fabric and preparation method thereof
CN121138026A